Gambaran makroskopik dan mikroskopik otot skelet pada hewan coba postmortem - Nelwan, Gabriella B.; Wangko, Sunny; Pasiak, Taufik F. (e-Biomedik, 2016)
Abstract: To make pathologists and law personnel aware of the importance of postmortem interval, published studies have reported a lot of methods for estimation of postmortem interval estimation of the remains. This study was aimed to obtain macroscopic and microscopic postmortem changes of skeletal muscle of two domestic pigs weighed 20 kg. This was a descriptive observational study. After the pigs were killed, death time, ambient temperature and humadity were noted. Postmortem evaluation were done at several time intervals, as follows: 30 minutes, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 9 hours, 12 hours, 15 hours, 18 hours, 21 hours, 24 hours, 30 hours, 36 hours, 42 hours, and 48 hours. The results showed that at 2 hours after death, the skeletal muscle became pale and soft progressively. The earliest microscopic change was identified at 30 minutes postmortem as pyknotic nuclei of skeletal muscles followed by hydrophic degeneration of muscle fibers and congestion of muscle tisue. At 12 hours until 48 hours postmortem, all microscopic changes became more distinct and widely distributed in nearly all muscle fibres. Albeit, the striated pattern and some normal muscle fibres could still be identified until 48 hours postmortem.Conclusion: Macroscopic changes could be identified the earliest at 2 hours postmortem and microscopic changes could be identified at 30 minutes postmortem.Keywords: macroscopic, microscopic, skeletal muscle, postmortem changesÂ Abstrak: Para peneliti telah banyak menggunakan metode-metode tertentu untuk membuat para penegak hukum dan ahli patologis lainnya memahami pentingnya penentuan jarak waktu kematian. Penelitian ini bertujuan untuk mengetahui gambaran perubahan makroskopik dan mikroskopik postmortem pada otot skelet hewan coba babi dengan massa tubuh lebih kurang 20 kg. Jenis penelitian ialah deskriptif observasional. Hewan coba dimatikan dengan cara ditusuk di bagian jantung, selanjutnya waktu kematian, suhu dan kelembaban ruangan dicatat. Otot skelet diamati pada beberapa interval waktu setelah kematian: 30 menit, 1 jam, 2 jam, 3 jam, 4 jam, 5 jam, 6 jam, 9 jam, 12 jam, 15 jam, 18 jam, 21 jam, 24 jam 30 jam, 36 jam, 42 jam dan 48 jam. Hasil penelitian mendapatkan bahwa otot skelet menjadi pucat dan lunak setelah 2 jam postmortem secara progresif. Pada 1 jam postmortem, tampak serat otot mengalami kongesti dan degenerasi hidropik. Perubahan mikroskopik tersebut menjadi lebih nyata dan tersebar luas di sebagian besar serat otot pada 12 jam sampai 48 postmortem. Walaupun demikian, corak seran lintang dan sebagian kecil serat otot masih tampak normal sampai 48 jam postmortem. Simpulan: Perubahan makroskopik telah dapat diidentifikasi pada 2 jam postmortem sedangkan perubahan mikroskopik mulai dapat diidentifikasi pada 30 menit postmortem.Kata kunci: makroskopik, mikroskopik, otot skelet, perubahan setelah kematian